Recommendations for the formation of a group of experts to determine the source data during the analysis of the interaction of government departments and the National Guard of Ukraine and State Emergency Service of Ukraine in case of emergency - Neklonsky І. М. (Honor and Law, 2019)
The recommendations on the formation of quantitative and qualitative composition of the working group of experts to determine the source data during the analysis of the interaction of government departments and the National Guard of Ukraine and State Emergency Service of Ukraine in case of emergency.